Development of techniques to predict and prevent both the effect of xenobiotics and their migration into pig-derived products - Nanka, Oleksandr; Chalaya, Olga; Nagornij, Sergiu; Chalyi, Oleksandr (Eastern-European Journal of Enterprise Technologies, 2018)
This paper reports research into the influence of heavy metals, specifically cadmium and plumbum, on the body of young pigs, and the effectiveness of the preparation to prevent intoxication with heavy metals. Heavy metals were fed separately and jointly, in doses that exceed the maximum permissible concentrations in fodder by 10 and 20 times. Thus, we have simulated the process of intoxication of a biological object (pigs) with heavy metals, which could happen as a result of environmental pollution. The study was carried out to determine the direction and degree of influence of heavy metals on the live weight, the weight of internal organs of animals, the degree of accumulation in pig production, as well as determining the effectiveness of an anti‒toxic additive that acts as a heavy metals detoxicant. Statistical processing of the acquired data made it possible to construct mathematical model and to establish the correlation relationship between the studied factors. It was established that heavy metals exert a significant negative impact on the intensity of growth of animals with an elevated effect in proportion to the dose. This is confirmed by the high correlation connection between these attributes, the correlation coefficient (r) is equal to 0.854. Thus, the live weight of pigs at the end of the experiment both in series I and II under the action of chemotoxicants reduced by 5.5‒14.8 % in comparison control. The strength of the impact depended on the toxin itself. Thus, the greatest negative effect was observed under the action of cadmium alone, as well as cadmium and plumbum together. The animals that received, against the background of intoxication with plumbum and cadmium, the antitoxic fodder additive, maintained the intensity of growth at the level of control, while, based on the results of series I, outperformed its indicators. Heavy metals mostly accumulated in the liver and kidneys, with the lowest level in the lungs, heart, and muscles. The constructed regression equations demonstrated that the main influence on the increase in the content of cadmium and plumbum in organs and meat is exerted by a rising dose of the respective element in the fodder. The content of plumbum in fodder affected the content of cadmium in meat, an increase in its concentration led to a decrease in the content of cadmium in meat. The research data obtained allow better understanding of the direction and the extent of effect of heavy metals on biological objects. Mathematical models could be employed to predict the content of toxins in pig products